To rearrange the equation \( y = mx + b \) so we can find \( m \), follow these easy steps:
-
Start with the equation: \[ y = mx + b \]
-
Get rid of \( b \) by subtracting it from both sides. This helps us to move it away from \( m \): \[ y - b = mx \]
-
Now, let's find \( m \) by dividing both sides by \( x \). This will leave \( m \) by itself: \[ \frac{y - b}{x} = m \]
-
So, when we rearrange it, we get: \[ m = \frac{y - b}{x} \]
And that means you can find \( m \) using this formula: \[ m = \frac{y - b}{x} \]
It's like a special recipe for finding the slope when you have \( y \), \( b \), and \( x \)!